The Crisis of Local Autonomy in a Congregational Church Model - Sondakh, Alva M.S; Weol, Wolter Lagun; Tuela, Anita I. (Peneliti.net, 2025)
This study aims to evaluate the implementation of congregational church governance within KGPM “Eben Haezer” Pinabetengan and to assess the extent to which the local congregation exercises autonomy in church life. The research is motivated by the observed tension between the theological principles of congregationalism—which emphasize local church sovereignty, the priesthood of all believers, and collective deliberation—and the practical realities that reflect tendencies toward centralized authority. The research questions address: (1) how congregational governance is applied within KGPM, (2) what factors support or hinder its implementation, and (3) how the model is manifested in the case of the Eben Haezer congregation. A qualitative descriptive approach was employed, utilizing in-depth interviews, participant observation, and document analysis for data collection. Thematic analysis was conducted using the Miles and Huberman model, and data validity was ensured through methodological and source triangulation. Findings reveal that although KGPM structurally adheres to a congregational model, in practice, it has shifted toward a more hierarchical system. Congregants are not actively involved in decision-making processes, leadership evaluation, or ministry structuring. This lack of participation has led to a governance crisis, creating a growing disconnect between leadership and the congregation. While some church leaders justify top-down intervention as necessary for maintaining unity, such practices undermine the core values of congregationalism. This indicates a functional erosion of local church autonomy. The study concludes that a theological and structural reorientation within KGPM is urgently needed to reaffirm its foundational congregational principles—emphasizing participatory governance, spiritual equality, and servant leadership. Such reorientation is essential to preserve the church’s identity as an autonomous, Spirit-led community shaped through collective discernment.